SIFAT FISIK TANAH DYSTRUDEPTS DI BAWAH TEGAKAN KELAPA SAWIT (Elais guineensis Jacq.) FAKULTAS PERTANIAN UNIVERSITAS RIAU YANG DIAPLIKASI MULSA ORGANIKMucuna bracteata - Paskah Aleksandro; Wawan '; Wardati ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The purpose of this research was to determine the physical properties of acid Dystrudepts in the circle area of palm oil plant applied the organic mulch of Mucuna bracteata. Soil physical analysis carried out in the soil laboratory of Agriculture Faculty, University of Riau, on October 2014 to February 2015. Application of organic mulch Mucuna bracteata. This research was arranged on using Completely Rendomized Design (CDR) nonfactorial that consists of            4 treatments and 4 replications . The treatments consisted of M0 (0 kg/plant), M1 (15 kg/plant), M2 (30 kg/plant) and M3 (45 kg/ plant). Parameters measured were soil moisture, soil temperature, organic matter, bulk density, total of pore space and  infiltration. Research suggests that the application of organic mulch Mucuna bracteata increase soil organic matter and improving soil physical. Keywords : Soil Physical properties, Dystrudepts, Mucuna bracteata